Extracción semiautomática de atributos morfológicos de especies a partir de descripciones taxonómicas - Mora-Cross, María Auxiliadora (Instituto Tecnológico de Costa Rica., 2016)
Taxonomic literature keeps records of the planet's biodiversity and gives access to the knowledge needed for its sustainable management. Unfortunately, most of the taxonomic information is available in scientific publications in text format. The amount of publications generated is very large; therefore to process it manually is a complex and very expensive activity.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2016.
Keywords: Biodiversidad; Lenguaje natural; Informática; Taxonomía